Benvenuti nella città delle attrazioni - Bonifacio, Dario (Scenari, 2025)
The phenomenon of global mass tourism is strongly affected by a complex of socio-cultural dynamics that can be summarized under the term “Disneyfication”. The modern tourist is essentially a consumer of emotions and experiences to be documented, and his view of art, landscape, and history is deeply shaped by a set of icons and desires acquired through permanent exposure to the forms of the entertainment industry. As the historic center acquires the functions and appearance of a theme park, i.e., a space apart from the rest of the city, protected by a series of control devices and stocked with a variety of paid family entertainment products centered on edutainment technology, the new urban redevelopment projects materialize the utopia of a perfect world, where luxury and well-being meet the needs of an individual in search of personal fulfillment.